Impact of the Village Alive Development Initiative on Poverty Reduction Among Farming Households in Kwara State, Nigeria - Oluwasegun Ayodeji Alalade; Morenike Peju Longe; Oloruntoba Luke Adebisi; Oluwatoki Peter Popoola; Tolulope Olamide Ladipo (Journal of Agricultural Extension, 2019)
This paper examined the impact of the Village Alive Development Initiative on poverty reduction in Kwara State, Nigeria. Two hundred and Fourteen (214) farming households were selected from the participating villages in Kwara State. Data were collected using structured interview schedule and were analyzed through the use of frequency count, simple percentages and propensity score matching technique. The results showed that the income level of participating farmers was significantly higher than that of non-participants. Furthermore, farm size, years of education and access to loan facilities negatively influence poverty, while, it was also revealed that VADI programme has led to poverty reduction among participating farming household hence such initiative as VADI should be encouraged and sustained among farming households in the study area.